Implementasi Akuntansi Syariah Akad Istishna Pada System Pre Order Studi Kasus Jual Beli Online Marketplace Shopee - Laila Khusnul Khotimah; Zulfa Nur Angraini; Asiyah Intan Nurfianti; Megania Kharisma (Ekopedia: Jurnal Ilmiah Ekonomi, 2025)
This study aims to determine the implementation of Sharia Accounting for the Istishna' Contract in the Pre-Order System in the Shopee Online Marketplace. This study uses a qualitative method with a descriptive approach. Based on the results of the study regarding the implementation of the Istishna' contract in the pre-order (PO) system on the Shopee marketplace, it can be concluded that the PO practice on the platform can be recommended as an Istishna' contract, but only under certain conditions. This conclusion was obtained through an analysis of Sharia theory, PSAK 104, field observations, and interviews with Shopee sellers and buyers.